‘By Grade 5, learners can read, right?’: Examining the reading ability of Namibian learners - Liswaniso, B.L. (Namibian Journal for Research, Science and Technology, 2024)
By Grade 4, English as a second language (ESL) learners are expected to read fluently and be able to read to learn from their grade-appropriate texts. The purpose of this article was to examine the reading ability of learners in Namibian schools (in the Zambezi Region), with a view to enhance the learners’ literacy levels. A quantitative research method was used in which three literacy tests were used in four schools to assess 365 Grade 5 learners’ decoding and reading comprehension levels. The analysis of the results showed that the learners had low decoding and reading comprehension skills. Considering the low reading levels of the learners, it seems the schools do not provide effective instructional practices. The results suggest that there is a need to improve learners’ reading comprehension levels through teacher empowerment to enhance their instructional practices.